(untitled) (VED International Journal of Arts, Commerce and Technology (VIJACT), 2026)
Firdaus Kanga’s Trying to Grow presents a sensitive and insightful exploration of disability, identity, and familial relationships within the socio-cultural framework of Indian society. The novel portrays the life of Brit Kotwal, a physically disabled Parsi boy, whose experiences reveal the emotional, psychological, and social dimensions of familial care. This study examines how family functions simultaneously as a source of support, protection, restriction, and emotional conflict in the narrative. Kanga highlights the complexities of caregiving through the attitudes of parents, relatives, and society toward disability, emphasizing both compassion and control. The novel also reflects the tension between dependence and the desire for individuality experienced by disabled individuals within family structures. Through humor, irony, and autobiographical elements, Kanga challenges stereotypical perceptions of disability and exposes the limitations of socially conditioned care. The study further explores how familial care influences self-esteem, emotional development, and personal freedom in the protagonist’s life. By analyzing the representation of care, affection, overprotection, and emotional neglect, the paper argues that Trying to Grow redefines disability discourse through a humanistic and socially critical perspective. The novel ultimately advocates dignity, emotional acceptance, and autonomy for differently-abled individuals within family and society.